THE IMPACT OF PROTESTANTISM ON THE ECONOMY OF THE COHO CHIL PEOPLE IN LAM DONG PROVINCE - Mai, Minh Nhat (Trường Đại học Đà Lạt, 2023)
This study examines the relationship between Protestantism and the Coho Chil economy using qualitative methods to analyze data from fieldwork in the Coho Chil Protestant communities of Lam Dong Province. The research shows that Protestantism has a positive impact on the economy of the Coho Chil community. This impact is manifested in casting out superstitious and magical practices and in applying economic rationalization. The Protestant doctrine and sermons by clergy have influenced the thinking of the people and their economic performance. Protestantism creates a social network and social capital that not only influences their economic life, but also provides timely material support for Christians in need. This paper serves as an additional resource for research related to the relationship between religion and the economy – an intriguing topic that is not found in much previous research in Vietnam.